Vascular Biochemistry 2003
DOI: 10.1007/978-1-4615-0298-2_23
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and mitochondrial oxidative stress: A study using heart mitochondria from the diabetic Goto-Kakizaki rat

Abstract: Increasing evidence shows that the overproduction of reactive oxygen species, induced by diabetic hyperglycemia, contributes to the development of several cardiopathologies. The susceptibility of diabetic hearts to oxidative stress, induced in vitro by ADP-Fe 2+ in mitochondria, was studied in 12-month-old Goto-Kakizaki rats, a model of non-insulin dependent diabetes mellitus, and normal (non-diabetic) Wistar rats. In terms of lipid peroxidation the oxidative damage was evaluated on heart mitochondria by measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 43 publications
2
39
1
Order By: Relevance
“…The inner mitochondrial membrane is believed to be particularly susceptible to oxidative damage even under physiological conditions, for it is a major site where ROS, and a high content of polyunsaturated fatty acids, accumulate and react with each other, thus yielding a large amount of stronger lipid peroxidation products which incur alterations in the structure integrity of mitochondrial membranes, causing irreversible swelling and disruption. A previous study demonstrated that oxidative stress induced in vitro by ADP-Fe 2+ in mitochondria strongly initiated a significant increase of lipid peroxidation (measured by O 2 consumption and thiobarbituric acid reactive species formation) and concurrent increase of mitochondria volume [20] . Another study proves that antioxidative agents such as Ginkgo biloba extract (EGb 761) succeeds in protecting mitochondria in cells of liver and heart from enlarging using diabetic model animals [20,21] .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The inner mitochondrial membrane is believed to be particularly susceptible to oxidative damage even under physiological conditions, for it is a major site where ROS, and a high content of polyunsaturated fatty acids, accumulate and react with each other, thus yielding a large amount of stronger lipid peroxidation products which incur alterations in the structure integrity of mitochondrial membranes, causing irreversible swelling and disruption. A previous study demonstrated that oxidative stress induced in vitro by ADP-Fe 2+ in mitochondria strongly initiated a significant increase of lipid peroxidation (measured by O 2 consumption and thiobarbituric acid reactive species formation) and concurrent increase of mitochondria volume [20] . Another study proves that antioxidative agents such as Ginkgo biloba extract (EGb 761) succeeds in protecting mitochondria in cells of liver and heart from enlarging using diabetic model animals [20,21] .…”
Section: Discussionmentioning
confidence: 96%
“…A previous study demonstrated that oxidative stress induced in vitro by ADP-Fe 2+ in mitochondria strongly initiated a significant increase of lipid peroxidation (measured by O 2 consumption and thiobarbituric acid reactive species formation) and concurrent increase of mitochondria volume [20] . Another study proves that antioxidative agents such as Ginkgo biloba extract (EGb 761) succeeds in protecting mitochondria in cells of liver and heart from enlarging using diabetic model animals [20,21] . Ang II increases NADPH oxidase activity and decreases NO levels, and both lead to aggravation of oxidative stress.…”
Section: Discussionmentioning
confidence: 96%
“…In recent years there has been increasing interest in the mitochondrion as numerous important physiological functions and disorders have been linked to this organelle (1)(2)(3). Malfunctioning mitochondrial metabolism is known to play a role not only in rare childhood diseases but also in many leading causes of death including heart disease, diabetes, and Parkinson's disease.…”
mentioning
confidence: 99%
“…MPTP induction would not be hindered by the increased amount of vitamin E, whose main role would be to decrease lipid peroxidation, but not oxidative phenomena that lead to MPTP opening. As proposed in previous published works [13,14], the increased oxidative stress observed in diabetic rats is probably contributing to an adaptive increase in mitochondrial amounts of coenzyme Q and vitamin E. A recent investigation done in the heart mitochondria from GK rats showed a lower amount of coenzyme Q9 [16]. This was suggested to be responsible for an increased susceptibility of diabetic heart mitochondria to oxidative damage.…”
Section: Discussionmentioning
confidence: 60%